How can you rewrite this trigonometric expression as an algebraic expression?

#cos(sin^-1(u)-cos^-1(v)#

#cos(sin^-1(u)-cos^-1(v)#

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

2
Mar 9, 2018

Answer:

#cos(sin^(-1)u-cos^(-1)v)=vsqrt(1-u^2)+usqrt(1-v^2)#

Explanation:

Let #sin^(-1)u=A# and #cos^(-1)v=B#

then #sinA=u#, which means #cosA=sqrt(1-u^2)#

and #cosB=v#, which means #sinB=sqrt(1-v^2)#

Hence, #cos(sin^(-1)u-cos^(-1)v)#

= #cos(A-B)#

= #cosAcosB+sinAsinB#

= #sqrt(1-u^2)xxv+uxxsqrt(1-v^2)#

= #vsqrt(1-u^2)+usqrt(1-v^2)#

Was this helpful? Let the contributor know!
1500
Impact of this question
48 views around the world
You can reuse this answer
Creative Commons License